2020
DOI: 10.3390/ijms21165757
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variants Contributing to Combined Pituitary Hormone Deficiency

Abstract: Combined pituitary hormone deficiency represents a disorder with complex etiology. For many patients, causes of the disease remain unexplained, despite usage of advanced genetic testing. Although major and common transcription factors were identified two decades ago, we still struggle with identification of rare inborn factors contributing to pituitary function. In this report, we follow up genomic screening of CPHD patient cohort that were previously tested for changes in a coding sequences of genes with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The possibility cannot be ruled out that monogenetic diseases and oligogenic abnormalities may be associated with the disease ( 65 ). Moreover, the results of a recent study revealed copy-number variants in several genes that might contribute to the formation of CPHD ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility cannot be ruled out that monogenetic diseases and oligogenic abnormalities may be associated with the disease ( 65 ). Moreover, the results of a recent study revealed copy-number variants in several genes that might contribute to the formation of CPHD ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lhx4 is critical to pituitary development 43 , 44 . Besides, the mutation of human LHX4 is usually associated with CPHD (characterized by a deficiency of the growth hormone and growth retardation) 32 , 45 , 46 . As a result, we speculated that lhx4 knockdown via MO in zebrafish is phenotypically similar to human CPHD.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted on DNA extracted from peripheral blood, using the phenol-chloroform method. A highresolution microarray scanning for genomic imbalances was conducted with the use of Affymetrix CytoScanHD arrays (2,7 M, Santa Clara, USA) and GeneChip Scanner 3000 7G (Budny et al 2020a). For an assay, 200 ng of genomic DNA was used.…”
Section: Genetic Testingmentioning
confidence: 99%